The handbook of management fads survival in business-- without taking yourself too seriously - Morris, Steve (Thorogood, 1998)
Management is an essential aspect of modern working life, but it can sometimes be taken rather too seriously by commentators and business analysts. For many people this is an unfortunate tendency and for them Steve Morris has written a wise but humorous book about management fads--past and present.